Law as metaphor from Islamic courts to the Palace of Justice - Starr, June (State University of New York Press, 1992)
This book explains the growth of secular law in a Middle East nation, revealing it to be the product of elite competition over control of the state, a competition the secular elites won in Turkey when Ataturk set up the new Republic.